As empresas e as urnas: a interferência do poder econômico no processo eleitoral - Lizardo, Filippe Soares (2023)
This thesis analyzes business activity based on its overlap with political activity, examining the participation of companies in the process of financing parties and candidacies. The aim is to verify the foundations and consequences of the decision of the Federal Supreme Court that judged the model of company participation in Brazilian political financing to be unconstitutional. The data collected in this study indicate that this judgment significantly changed the political financing regime adopted by Brazil, beyond the immediate effect of preventing companies from participating in the electoral process, producing positive structural changes in the systematic collection and application of resources in campaigns, in special for inducing the migration of the political financing matrix, previously mostly private and, currently, fundamentally based on public revenues. In addition to reducing the influence of companies' economic power in elections, the Federal Supreme Court's decision also resulted in the Legislative Branch acting to give new meaning to the regulation of Brazilian political financing, through changes in some of the main premises that supported the financing model. then in force. Comparative calculations were carried out using the Electoral Court database, which indicated a decrease in the concentration of resources in elections in which the ban on corporate donations came into force.